2022
DOI: 10.1101/2022.12.16.520739
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of PatIent-Level distances from single cell genomics and pathomics data with Optimal Transport (PILOT)

Abstract: Although clinical applications represent the next challenge in single-cell genomics and digital pathology, we are still lacking computational methods to analyse single-cell and pathomics data at a patient level for finding patient trajectories associated with diseases. This is challenging as a single-cell/pathomics data is represented by clusters of cells/structures, which cannot be easily compared with other samples. We here propose PatIent Level analysis with Optimal Transport (PILOT). PILOT uses optimal tra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…These limitations, however, are shared across current tissue-centric tailored methods. In contrast, models based on generative deep learning (De Donno et al , 2022; Boyeau et al , 2022) and the Wasserstein metric (Joodaki et al , 2022; Chen et al , 2020) can take advantage of single-cell measurements to estimate sample-level heterogeneity, but the interpretability of their estimated latent space is limited in comparison to the MOFA models, where features and cell-types can be associated with each factor.…”
Section: Discussionmentioning
confidence: 99%
“…These limitations, however, are shared across current tissue-centric tailored methods. In contrast, models based on generative deep learning (De Donno et al , 2022; Boyeau et al , 2022) and the Wasserstein metric (Joodaki et al , 2022; Chen et al , 2020) can take advantage of single-cell measurements to estimate sample-level heterogeneity, but the interpretability of their estimated latent space is limited in comparison to the MOFA models, where features and cell-types can be associated with each factor.…”
Section: Discussionmentioning
confidence: 99%
“…The same study also showed that pathomics data can be used for predictive modeling of long-term kidney survival in Immunoglobulin A-Nephropathy (IgAN) patients and showed the applicability of pathomics for complex biocomputation analysis used in other OMICs-fields, such as transcriptomics. This analysis delineated a trajectory of glomerular morphometric progression of IgAN-patient with progressive tuft deformation [6 ▪▪ ,21].…”
Section: Deep Learning Applications In Nephropathologymentioning
confidence: 99%
“…Recently, Patient level distance with Optimal Transport (PILOT) ( [19]) has been proposed to investigate the patient level distance using the Wasserstein distance. Compared to PILOT, our method (QOT-Adaptive) could be seen as the generalized version of PILOT.…”
Section: Link To Relevant Prior Workmentioning
confidence: 99%